MEKANISME PSIKOLOGIS DAN SOSIAL DALAM PEMBENTUKAN PERILAKU KONSUMEN BERKELANJUTAN(Sebuah Studi Literatur) - Komang Junita Widhipratiwi; Gangsar Parikesit; Luhde Hendryani Pratiwi; Benny Fernando Panjaitan; Putu Yudi Setiawan; Ni Nyoman Kerti Yasa (Adisam Publisher, 2026)
Sustainable consumer behaviour has become a key issue in the study of marketing and sustainability, in line with growing public awareness of the environmental impact of consumption. Various studies indicate that consumer behaviour is influenced by psychological and social factors that interact with one another in the decision-making process. This study aims to develop a conceptual model explaining the role of psychological and social factors in shaping sustainable consumer behaviour through a literature review approach. The method employed is an exploratory literature study utilising narrative synthesis and conceptual mapping techniques. The primary sources consist of four academic articles discussing motivation, consumer engagement, social norms, emotions and attitudes in the context of sustainable consumption behaviour. The results of the synthesis indicate that consumer motivation and engagement act as psychological factors driving sustainable consumption behaviour, whilst social norms act as social factors influencing behaviour both directly and through emotions and attitudes. Based on the integration of these findings, this study produces a conceptual model proposing eight theoretical propositions regarding the relationships between variables. The contribution of this research lies in the integration of psychological and social factors within a single, more comprehensive framework to explain sustainable consumer behaviour. The resulting model is expected to serve as a foundation for further empirical research and to provide insights for companies and policymakers in promoting more responsible and sustainable consumption.